2010
DOI: 10.1074/jbc.m110.129718
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Wasting in Aged, Sarcopenic Rats Is Associated with Enhanced Activity of the Ubiquitin Proteasome Pathway

Abstract: Among the hallmarks of aged organisms are an accumulation of misfolded proteins and a reduction in skeletal muscle mass ("sarcopenia"). We have examined the effects of aging and dietary restriction (which retards many age-related changes) on components of the ubiquitin proteasome system (UPS) in muscle. The hindlimb muscles of aged (30 months old) rats showed a marked loss of muscle mass and contained 2-3-fold higher levels of 26S proteasomes than those of adult (4 months old) controls. 26S proteasomes purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
155
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(173 citation statements)
references
References 86 publications
12
155
3
1
Order By: Relevance
“…Since muscle wasting was reduced in these animals, these findings suggest that the buildup of proteasomes contributes to the loss of muscle mass in aged animals. In support of this notion we found that the levels of proteasome subunits in aged skeletal muscle were inversely correlated with muscle weight (subunits 1: r=-0.71, p<0.05; 5: r=-0.69; p<0.05), and no such inverse relationship was found in muscles of adult rats or aged animals maintained on dietary restriction (Altun et al, 2010). However, the underlying mechanism of this accumulation remains unclear.…”
Section: Activation Of the Ups In Sarcopeniamentioning
confidence: 59%
See 3 more Smart Citations
“…Since muscle wasting was reduced in these animals, these findings suggest that the buildup of proteasomes contributes to the loss of muscle mass in aged animals. In support of this notion we found that the levels of proteasome subunits in aged skeletal muscle were inversely correlated with muscle weight (subunits 1: r=-0.71, p<0.05; 5: r=-0.69; p<0.05), and no such inverse relationship was found in muscles of adult rats or aged animals maintained on dietary restriction (Altun et al, 2010). However, the underlying mechanism of this accumulation remains unclear.…”
Section: Activation Of the Ups In Sarcopeniamentioning
confidence: 59%
“…A growing body of evidence suggests that loss of muscle mass in elderly occurs through mechanisms more complex than those involved in disuse and disease atrophy in younger individuals (Altun et al, 2010;Edstrom et al, 2007;Edstrom and Ulfhake, 2005). In humans and rodents alike, a number of mechanisms have been suggested to underpin sarcopenia: 1) loss of innervation 2) disuse 3) impaired maintenance and repair including decline in endo-, para-and autocrine signaling (e.g.…”
Section: Regulation Of Muscle Mass and Tentative Mechanisms In Sarcopmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased proteasome activity in human muscles is age‐associated,12 whereas in rats, proteasome activity in muscles increases with age 13. We reported that proteasome activity is reduced in a mouse model for muscle ageing 14.…”
Section: Introductionmentioning
confidence: 80%